2012
DOI: 10.1590/s1984-29612012000300003
|View full text |Cite
|
Sign up to set email alerts
|

Polymerase chain reaction and real-time PCR for diagnosing of Leishmania infantum chagasi in dogs

Abstract: The importance of dogs as a reservoir for Leishmania infantumchagasi in urban environments has stimulated numerous studies assessing diagnostic techniques. When performed properly, such procedures are an important step in preventing leishmaniasis in humans. Molecular methods have become prominent for this purpose. The aim of the present study was to determine the performance of the polymerase chain reaction (PCR) and real-time PCR (qPCR) for diagnosing of canine visceral leishmaniasis (CVL) using different bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 19 publications
1
14
1
Order By: Relevance
“…Different studies have demonstrated high positive rates of L. infantum detection in lymph nodes (IKONOMOPOULOS et al, 2003), spleen (SOLCÀ et al, 2012) and bone marrow (FERREIRA et al, 2012) using molecular biology tests. Some of them have suggested that lymph nodes are the best biological samples for molecular diagnosis of L. infantum (IKONOMOPOULOS et al, 2003;RAMOS et al, 2012). Nonetheless, few studies on parasite load quantification have been conducted, even though such information is extremely important for correctly choosing the sample to be used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different studies have demonstrated high positive rates of L. infantum detection in lymph nodes (IKONOMOPOULOS et al, 2003), spleen (SOLCÀ et al, 2012) and bone marrow (FERREIRA et al, 2012) using molecular biology tests. Some of them have suggested that lymph nodes are the best biological samples for molecular diagnosis of L. infantum (IKONOMOPOULOS et al, 2003;RAMOS et al, 2012). Nonetheless, few studies on parasite load quantification have been conducted, even though such information is extremely important for correctly choosing the sample to be used.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, obtaining lymph node aspirates not only is easier from a practical point of view but also demonstrates the greater viability of this biological sample over bone marrow and spleen samples. In addition, this biological sample (lymph node) has been demonstrated to be useful for detecting the protozoon, independently of the animal's clinical status (RAMOS et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They were negative for Leishmania braziliensis. According to researchers [18], L. infantum is the main agent when PCR results are positive, especially in association with geographic localization of dogs, and presence of clinical signs. In addition, sera samples from 17 healthy dogs, negative for L. infantum (serologic and PCR), composed our negative control group.…”
Section: Animalsmentioning
confidence: 99%
“…Recently, PCR has significantly advanced with the use of quantitative real-time PCR (qPCR) that promotes a real-time and accurate quantification (Ramos et al 2012;Solc a et al 2012), and helps in confirmation of inconclusive cases of CVL, i.e. dogs not yet seroconverted, accurate detection of potential reservoirs, and determination of a decrease of the parasite load in these animals as a result of successful therapy.…”
Section: Introductionmentioning
confidence: 99%